En Route to Europe? The Anti-politics of Deportation from North Africa to Mali. Issue 5 (20th October 2022) - Sylla, Almamy; Cold-Ravnkilde, Signe Marie
ABSTRACT: In the last 30 years Europe has attempted to strengthen its territorial borders with Africa through new migration governance practices. This article takes its point of departure in recent mass expulsions of Malian migrants from Algeria to reception centres in Niger to analyse the interlinked processes of deportation from North Africa to Mali and the increased dissatisfaction among the deportees 'assisted' by EU funded return and reintegration programmes in Mali. Through the analytical lens of the 'anti-politics machine' (Ferguson 1996), the article argues that the attempts to transform European borderwork practices into a 'softer' and 'more humanist' approach to migration management create new, contested, border zones aiming to obstruct African migrants' mobility. The article shows how these new, EU-driven, migration management regimes, which are increasingly disconnected from local politics and mobility practices, spur contestations in Sahelian countries of origin, transit and reception. Thereby, the article provides insights into the unintended effects of how EU return governance is implemented, who it benefits, and who it leaves behind.